(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
N-Heterocyclic compounds are important organic molecules with wide applications in pharmaceuticals, agrochemicals, and functional materials. The growing need for efficient and sustainable synthetic methods has promoted the development of one-pot synthesis as a valuable approach for constructing diverse heterocyclic frameworks. This review discusses recent advances in one-pot strategies, including their principles, reaction mechanisms, catalytic systems, and applications. One pot synthesis One-pot synthesis enables multiple transformations in a single reaction vessel without isolating intermediates, offering advantages such as improved step economy, enhanced atom utilization, shorter reaction times, reduced solvent consumption, and minimal waste generation. The incorporation of green chemistry approaches, including eco-friendly solvents, recyclable catalysts, energy-efficient processes, and multicomponent reactions, has further improved the sustainability of these methods. Various catalytic systems, such as homogeneous, heterogeneous, organocatalytic, biocatalytic, and nanocatalytic approaches, have enhanced reaction efficiency and selectivity. Application The pharmaceutical importance of one-pot synthesized N-heterocycles in drug discovery and therapeutic development is highlighted, along with their applications in agrochemicals, materials science, combinatorial chemistry, and industrial synthesis. Although significant progress has been achieved, challenges including reaction optimization, substrate compatibility, selectivity control, and catalyst stability remain. Future advancements in sustainable catalysis and innovative reaction design are expected to expand the scope of one-pot synthesis as an efficient, economical, and environmentally friendly strategy for producing biologically and industrially relevant N-heterocyclic compounds.